2020
DOI: 10.1002/jum.15438
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Differentiation of Dural Arteriovenous Fistulas in the Transverse Sinus/Sigmoid Sinus and Cavernous Sinus Using Carotid Ultrasound

Abstract: Objectives Dural arteriovenous fistula (DAVFs) in the transverse sinus (TS)/sigmoid sinus (SS) and cavernous sinus (CS) are observed frequently in the clinic. This study aimed to detect DAVFs with ultrasound and compare carotid ultrasound findings between these conditions. Methods We retrospectively reviewed 26 patients with either a TS/SS DAVF or a CS DAVF who were admitted to our hospital for evaluation of DAVFs from 2014 to 2018. The shunt site decision was made by neuroendovascular experts, whereas carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The anastomoses formed between the occipital and ascending pharyngeal arteries with the branches of the MMA were the most likely explanation: the mastoid branch of the OA with the petrosquamous branch of the MMA and carotid and jugular ascending pharyngeal branches with the petrosal and petrosquamous MMA branches, respectively. 23 In the case of a dilated occipital artery, Hisaeda et al 26 found similar results when assessing this vessel in transverse-sigmoid lesions on ultrasound.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The anastomoses formed between the occipital and ascending pharyngeal arteries with the branches of the MMA were the most likely explanation: the mastoid branch of the OA with the petrosquamous branch of the MMA and carotid and jugular ascending pharyngeal branches with the petrosal and petrosquamous MMA branches, respectively. 23 In the case of a dilated occipital artery, Hisaeda et al 26 found similar results when assessing this vessel in transverse-sigmoid lesions on ultrasound.…”
Section: Discussionmentioning
confidence: 80%
“… 23 In the case of a dilated occipital artery, Hisaeda et al. 26 found similar results when assessing this vessel in transverse-sigmoid lesions on ultrasound.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…When performing the examination, extra care should be taken to rule out any additional conditions that could be causing similar hemodynamic abnormalities [3]: stenosis or occlusion of the CCA, proximal vertebral artery stenosis or occlusion, severe stenosis of the distal ICA or proximal middle cerebral artery, and highly vascularized head and neck tumors. Moreover, examination of the occipital arteries [5] may further aid diagnosis, especially in AVFs with lower shunt volume.…”
Section: Discussionmentioning
confidence: 99%